Micropore Characteristics and Geological Significance of Shale Reservoirs: Case Study of Fuling Shale Gas in Sichuan Basin, China. (27th May 2021) - Cheng, Liang; Guan, Fujia; Liu, Dehua; Yang, Wenxin; Sun, Jing
Abstract : Several techniques (such as scanning electron microscopy (SEM) and gas adsorption systems) have been used to study the pore features and structures of shale reservoirs. The available methods and techniques have restricted the specific research on micropores, and the morphology, genesis, volume, and main factors controlling pore characteristics are yet to be analyzed. Currently, there is no systematic understanding of the role that these spaces play in gas storage and flow. As such, our understanding of the spatial connectivity of pores and reserves of shale reservoirs is limited. In this study, the pores of the Fuling shale gas reservoir in the Sichuan Basin were systematically observed by SEM and transmission electron microscopy. Images of pores smaller than 2 nm were captured for the first time, and their morphology and genesis were analyzed by combining these images with the rock mineralogy theory. The pore size distribution characteristics of the reservoir were analyzed by the adsorption-mercury injection method and nuclear magnetic resonance, and the main factors controlling the distribution of different pore sizes were analyzed. The results show that large numbers of micropores were distributed between the mesopores and macropores in the shale reservoir, which mainly consisted intergranular pores, intermolecular pores, interlamellar pores of clay minerals, and organic matter skeleton pores. The development of pores smaller than 1 nm was mainly controlled by the clay mineral content, and the development of pores with a size of approximately 1-2 nm was related to the contents of clay minerals and organic matter. These pores could connect the macropores and mesopores well, which is important for gas storage and flow. In this paper, the types, distribution, and main controlling factors of micropores were studied, and our understanding of the reservoir space was improved from the nanometer level to the Angstrom level, which is important for gas storage and flow process analysis.